Changes in exercise capacity and anthropometric measures after Work It Out—a holistic chronic disease self-management program for urban Aboriginal and Torres Strait Islander people. (September 2019) - Hu, J.; Basit, T.; Nelson, A.; Bartlett, A.
Abstract: Objectives: The Work It Out (WIO) program is a holistic chronic disease self-management and rehabilitation program in Queensland that is tailored for urban Aboriginal and Torres Strait Islander people with/at risk of chronic disease. This study aimed to examine the overall changes in participants' exercise capacity and anthropometric measurements and to explore the correlations between these changes. Study design: Quasi-experimental prepost intervention study. Methods: A total of 406 participants self-identified as Aboriginal and Torres Strait Islander people, who had attended one or more cycles of the program from 2014 to 2017, were included. Health information from the last review assessment was compared with that of the initial assessment using paired t -tests. Multivariate regression models were applied to explore the associations between changes in 6-min walk distance (6MWD) and anthropometric measurements. Results: An increase in 6MWD (77 m, 95% confidence interval [CI]: 65, 90), as well as small reductions in waist circumference (WC) (−1.79 cm, 95% CI: −2.76 to −0.82) and hip circumference (−1.11 cm, 95% CI: −2.13 to −0.08) were identified. Statistically significant reductions were observed across all anthropometric measures in the respective highest tertiles (body mass index: −0.71, 95% CI: −1.35 to −0.07; weight: −2.59 kg, 95% CI: −4.84 to −0.34; WC: −5.09 cm, 95% CI: −6.99 to −3.20; waist to hip ratio: −0.033, 95% CI: −0.047 to −0.02). The increments of 6MWD in returning participants (92 m, 95% CI: 75 to 109) was found to be greater than those in one-off participants (59 m, 95% CI: 40–78). In particular, the percentage of 6MWD change from baseline was significantly correlated to the percentage of WC change after adjusting for age, gender, the number of pre-existing chronic conditions, and the number of cycles attended (coefficient: −1.33, 95% CI: −2.42 to −0.24). Conclusion: Significant improvement in functional exercise capacity and modest changes in anthropometric measurements were identified in WIO participants. WC change could be used as an indicator of the change of participants' six-minute walk distance. Findings may be useful for promoting and guiding similar health programs for improving chronic disease management in Australian Indigenous communities. Highlights: Significant increase in 6-min walk distance (6MWD) was identified in Work It Out (WIO) program participants. The increment in 6MWD was greater in returning participants than one-off participants. Slight reductions in waist circumference (WC), hip circumference, and waist to hip ratio were identified in some groups of WIO participants. WC change was associated with that of the six-minute walk distance.